Identification of wysPII as an Activator of Morphological Development in Streptomyces albulus CK-15 - Liu, Binghua; Ge, Beibei; Ma, Jinjin; Wei, Qiuhe; Khan, Abid Ali; Shi, Liming; Zhang, Kecheng (Frontiers in Microbiology, 2018)
Wuyiencin is produced by Streptomyces albulus var. wuyiensis and used widely in agriculture to control a variety of fungal diseases, such as cucumber downy mildew, strawberry powdery mildew, and tomato gray mold. As an industrially-produced biopesticide, reducing production costs is very important for popularization of this approach. To obtain a rapidly growing strain that effectively shortens the fermentation time, we investigated the effects of knockout and overexpression of the wysPII gene, a member of the LuxR regulatory gene family, in S. albulus strain CK-15. The ΔwysPII mutant exhibited a reduced rate of growth and sporulation. The time taken to reach the greatest mycelial biomass was approximately 18 h shorter in the ooPII (wysPII overexpressing) strain compared with that of the wild-type (WT) strain. In addition, the time to reach the greatest wuyiencin production was 56 h in the ooPII strain compared with 62 h in the WT strain. Furthermore, wysPII was shown to act as an activator of morphological development without affecting wuyiencin production. Thus, the ooPII strain can be used to reduce costs and increase efficiency in industrial fermentation processes for wuyiencin production.